1986
DOI: 10.3354/meps032229
|View full text |Cite
|
Sign up to set email alerts
|

Condition of Atlantic cod Gadus morhua larvae after the transition to exogenous feeding: morphometries, buoyancy and predator avoidance

Abstract: The condition of Atlantic cod Gadus morhua L. larvae reared in densities of 0, 2, 5 and 10 zooplankton ml-l was examined after the transition to exogenous feeding. Fulton's K (weight/length3) was not correlated with prey density in which larvae were reared, indicating that this index of condition is inappropriate for larvae immediately after yolk sac absorption. Fulton's K was also not positively correlated with the ability to avoid a simulated predator. However, predation avoidance was positively correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…Larvae with a low nutritional status will consequently be smaller, weaker and less developed with regard to sensory and locomotory capacities than well-fed larvae of the same age, thus being more susceptible to predation (but see Billerbeck et al, 2001). For a variety of fish species (herring, hake, cod, flounder, anchovy, striped bass), it has been shown that starved larvae are more susceptible to predation than fed larvae (Bailey, 1984;Neilson et al, 1986;Yin and Blaxter, 1987;Booman et al, 1991). Several studies indicate that high larval condition can be correlated with increased growth rate and enhanced recruitment or juvenile survival under natural conditions (Searcy and Sponaugle, 2001;Sponaugle et al, 2006), but few attempts have been made to correlate larval condition with any behavioural function critical for larval survival, such as swimming behaviour (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Larvae with a low nutritional status will consequently be smaller, weaker and less developed with regard to sensory and locomotory capacities than well-fed larvae of the same age, thus being more susceptible to predation (but see Billerbeck et al, 2001). For a variety of fish species (herring, hake, cod, flounder, anchovy, striped bass), it has been shown that starved larvae are more susceptible to predation than fed larvae (Bailey, 1984;Neilson et al, 1986;Yin and Blaxter, 1987;Booman et al, 1991). Several studies indicate that high larval condition can be correlated with increased growth rate and enhanced recruitment or juvenile survival under natural conditions (Searcy and Sponaugle, 2001;Sponaugle et al, 2006), but few attempts have been made to correlate larval condition with any behavioural function critical for larval survival, such as swimming behaviour (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Predation and starvation are considered to be the 2 major causes of mortality in larval fishes (Miller et al 1988, Bailey & Houde 1989. These 2 factors can act together to increase mortality rates, as starved or underfed larvae may be more susceptible to predation (Neilson et al 1986). Some evidence suggests that general activity or vertical migratory activity declines in starved larvae of several species (Laurence 1972, Blaxter & Ehrlich 1974.…”
Section: Introductionmentioning
confidence: 99%
“…Negative residuals indicated larvae in poor condition relative to the overall average condition of the population during the sampling season. Comparative studies have shown that morphometric indices are generally good indicators of true condition as measured by histological or biochemical indices or of the known condition of starved larvae (Ehrlich et al 1976, Nielson et al 1986, Theilacker 1986, Yin & Blaxter 1986, SetzlerHamilton et al 1987.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid a systematic bias in morphometric measurements, all larvae were measured within an interval of 6 to 8 wk after capture and fixation. The residuals of the linear regression of body height above the anus (a dimension sensitive to starvation) against total length (a dimension less sensitive to starvation) were used to assess the relative emaciation of the yolk-sac larvae and postlarvae of a given species (Wyatt 1972, Ehrlich et al 1976, Koslow et al 1985, Nielson et al 1986, Yin & Blaxter 1986. Negative residuals indicated larvae in poor condition relative to the overall average condition of the population during the sampling season.…”
Section: Methodsmentioning
confidence: 99%